Polskie tłumaczenia hymnu św. Tomasza z Akwinu Adoro te devote w katolickich śpiewnikach - Garnczarski, Stanisław (Studia Pastoralne, 2026)
The origin of the Eucharistic hymns, including Adoro te devote of Saint Thomas Aquinas was the fruit of the Eucharistic devotion developed in the Middle Ages, which was manifested by the desire to see the Host and the establishment of the Feast of Corpus Christi. Research on the original anthem in Latin has collected three of its versions: Adoro te deuote, latens ueritas; Adoro te devote, latens Deitas; Adoro these supplex latens Deitas. It seems, however, that most of translations have Adoro te devote, latens Deitas as a model. Author of the study found 7 versions of the translations of this hymn. They are preserved in collections of varying provenance, both temporal and territorial.Translations generally differ in the size of the verses. Are used texts included 11-, 12- and 13-syllable. The stanzas are 4-line, with female rhymes, perfect and contiguous: aabb. The number of versions of the hymn Adoro te devote in Polish translation testifies to the great popularity of this hymn among the faithful.